THE FOUNDATIONS OF UNIVERSAL CIVILIZATION CONSCIOUSNESS TOWARDS THE CULTURAL EVOLUTION - Lütfi ŞEYBAN (Fırat University, 2019)
It is generally accepted that a real, scientific and cultural movement in the Islamic world in the late Ottoman period were depleted substantially productivity. However, a nation's place in the world is determined through this science-culture movement. As a result of this cultural vitality and sustain the productivity of Muslims, they as soon as began weakening against its rivals in every way. So they destroyed and defeated by rival forces. Today, according to one view, they are driven to extinction, or they are experiencing a resurgence according to another opinion. In any event, today and for the future, members of the Islamic world should put the Islamic heritage they inherited in their daily life in a contemporary format. And that they have to build a respectable presence in the world with the power they receive from their heritage. Here, there is a scientific name to build their presence is built civilization and there is a scientific basis for it. In this study, the principles and conditions of the civilization-building process is discussed in terms of a person's self-development. Because social changes in this age, rather it is possible by personal improvement of members.